2018
DOI: 10.1186/s13059-018-1528-8
|View full text |Cite
|
Sign up to set email alerts
|

Genomic approaches for studying crop evolution

Abstract: Understanding how crop plants evolved from their wild relatives and spread around the world can inform about the origins of agriculture. Here, we review how the rapid development of genomic resources and tools has made it possible to conduct genetic mapping and population genetic studies to unravel the molecular underpinnings of domestication and crop evolution in diverse crop species. We propose three future avenues for the study of crop evolution: establishment of high-quality reference genomes for crops and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 233 publications
(235 reference statements)
0
52
0
Order By: Relevance
“…The genetic study of populations is a main approach for analysing crop evolution and domestication (Schreiber et al, 2018). The published cotton reference genomes of G. hirsutum and G. barbadense (Hu et al, 2019;Wang et al, 2019) have significantly contributed to our knowledge of cotton population genetics, and have allowed for the dissection of complex traits, in addition to uncovering domestication signatures and large-scale genetic variations (Wang et al, 2015;Wang et al, 2017;Ma et al, 2018;Wen et al, 2018;Wen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The genetic study of populations is a main approach for analysing crop evolution and domestication (Schreiber et al, 2018). The published cotton reference genomes of G. hirsutum and G. barbadense (Hu et al, 2019;Wang et al, 2019) have significantly contributed to our knowledge of cotton population genetics, and have allowed for the dissection of complex traits, in addition to uncovering domestication signatures and large-scale genetic variations (Wang et al, 2015;Wang et al, 2017;Ma et al, 2018;Wen et al, 2018;Wen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The last few years have seen a tremendous advance in plant genomic sciences driven by technologies such as long read PacBio and lately Oxford Nanopore sequencing (Bolger et al , 2019) as well as new technologies to obtain long range structural information such as optical mapping and Hi-C based information (Schreiber, Stein and Mascher, 2018) . Indeed, it has been shown that these technological advances can be used to get (near) chromosome scale assemblies of sub-Gigabase genomes (Belser et al , 2018) and that they are particularly useful to unravel the genomes of wild species which are close relatives of important crops providing information about exotic germplasm and its use (Wu et al , 2018) .…”
Section: Discussionmentioning
confidence: 99%
“…Plants sometimes transmit somatic mutations to their descendants asexually or sexually (in case when flower buds developments in somatically mutated part of plant). Mutations create variations in the gene pool, and the less favorable (or deleterious) mutations are removed from the gene pool by natural selection, while more favorable (beneficial or advantageous) ones tend to accumulate, resulting in evolutionary change [6]. Irradiation has been successfully used for mutation breeding in various crops and ornamental plants [37] and has proven an adept means of encouraging the expression of recessive genes and producing new genetic variations [23,[36][37][38].…”
Section: Introductionmentioning
confidence: 99%